Use of patient- handling devices and coworker assistance in long-term care settings: A cross-sectional study - Minjung Kyung; Soo-Jeong Lee; Laura M. Wagner; OiSaeng Hong (International Journal of Nursing Studies Advances)
Background: Although many patient handling activities require use of lifting devices and assistance from coworkers to ensure safety and efficiency, integrating these practices into the workplace remains challenging. Objective: The objectives of this study were to examine the association of musculoskeletal symptoms with the use of patient -handling devices or coworker assistance and to identify factors associated with their adoption among direct care workers in long-term care facilities. Methods: A cross-sectional study was conducted among 376 direct care workers recruited from 19 long-term care facilities in South Korea. Chi-square tests and analysis of variance with Tukey post-hoc analysis were used to assess differences in musculoskeletal symptom prevalence, frequency, and severity by patient handling methods. Multiple logistic regression was used to examine the relationship between the use of coworker assistance or patient -handling devices and demographic, job-related, physical, and psychosocial work factors and perception of management's safety priority. Results: The majority of participants were female, married, and employed in non-permanent positions. Among the participants, 42.2% used both patient- handling devices and coworker assistance, 5.8 % used only patient- handling devices, 24.7 % used only coworker assistance, and 27.3 % used neither method. Workers who used both methods reported a significantly lower prevalence, frequency, and severity of musculoskeletal symptoms compared to those who relied on only one method or neither. Older and immigrant workers were less likely to use patient- handling devices. While workers perceiving management having a high priority for safety were more likely to use coworker assistance, immigrant, non-permanent, and overcommitted workers and those with longer years in long-term care showed lower tendencies to seek coworker assistance. Conclusion: Despite the musculoskeletal benefits of using patient- handling devices and coworker assistance, their availability and adoption remain insufficient in long-term care facilities in Korea. These findings underscore the vital role that nursing leaders may play in promoting the adoption of combined patient handling methods, particularly among vulnerable worker groups. Empowerment strategies, such as fostering a supportive work environment and addressing barriers faced by overcommitted, long-tenured, and marginalized workers, may be essential to improving the safety and well-being of both patients and staff in long-term care settings.